Determinan Nilai Perusahaan dengan Harga Saham Sebagai Variabel Intervening - Donianto Tandi Patiku; Muhammad Su’un; Andika Pramukti (Departement of Mathematics Education, 2023)
This study aims to determine of firm value with firm price as intervening variable. This research was conducted on the official website Indonesia Stock Exchange (IDX) namely www.idx.co.id by using secondary data sourced from company financial reports registrered on the official IDX website, news, journals, and books related to sharia financial and accounting report analysis. This study uses quantitative methods. The analysis technique used is ultiple linear regression with statistical software Smart PLS 4.0. The results of this study indicate that the determinant of firm value with firm price as an intervening variable indicates that the research conducted has an effect on capital structure on stock price and capital strukture has an effect on firm value which is mediated by stock prices and stock prices have an influence on firm value. So this study explains that capital structure is a determinant that has more influence on firm value mediated by firm prices.